Fabrication and compatibility evaluation of polycaprolactone/hydroxyapatite/collagen-based fiber scaffold for anterior cruciate ligament injury - Aminatun, None; Hanum S, Faika; Izak R, Djoni; Hadi, Sofijan; Amrillah, Tahta; Che Abdullah, Che Azurahanim (Royal Society of Chemistry, 2023)
Knee injuries are musculoskeletal system injuries, including the Anterior Cruciate Ligament (ACL). ACL injuries are most common in athletes. This ACL injury necessitates biomaterial replacement. It is sometimes taken from the patient's tendon and a biomaterial scaffold is used. The use of biomaterial scaffolds as artificial ACLs remains to be investigated. The purpose of this study is to determine the properties of an ACL scaffold made of polycaprolactone (PCL)-hydroxyapatite (HA) and collagen with various composition variations of (50 : 45 : 5), (50 : 40 : 10), (50 : 35 : 15), (50 : 30 : 20), and (50 : 25 : 25) wt%. The scaffold was created using the electrospinning method with a voltage of 23 kV, a needle-collector distance of 15 cm, and a solution flow rate of 2 mL h−1. The average fiber diameter in all samples was less than 1000 nm. The model with the best characterization was PCL : HA : collagen with a weight-to-weight (wt%) ratio of 50 : 45 : 5 and an average fiber diameter of 488 ± 271 nm. The UTS and modulus of elasticity for braided samples were 2.796 MPa and 3.224 MPa, respectively, while the non-braided samples were 2.864 MPa and 12.942 MPa. The estimated time of degradation was 9.44 months. It was also revealed to be non-toxic, with an 87.95% viable cell percentage.